Botryoid-shaped nanoparticles-enhanced ELISA for ochratoxin A. Issue 2 (4th March 2017) - Zhu, Yan; Liu, Chun-Li; Xie, Zheng-Jun; Liu, Li-Qiang; Peng, Chi-Fang; Xue, Feng
ABSTRACT: Botryoid-shaped Au/Ag nanoparticles (BSNPs) were prepared with a tailored galvanic reaction. Ag nanoprisms–BSA complex were employed as a template to react with HAuCl4 in the presence of ascorbic acid. The BSNPs–HRP–IgG about 40 nm were used as the carriers of HRP–IgG for amplifying the detection signal of an indirect competitive ELISA against ochratoxin A. This BSNPs-enhanced ELISA method achieved an IC20 of 0.016 ng/mL and an IC50 of 0.05 ng/mL, which were 30 times more sensitive than conventional ELISA. The application of BSNPs to the enhanced ELISA showed acceptable reproducibility, stability and could be applied to determine other harmful small molecules in food.